The Influence of Leg Muscle Exercises on the Taekwondo Kick Speed Technique of Dollyo Chagi at the Pontianak City NTC Club - Rio Wardhani; Stephani Yane (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. (1) this study aims to determine the effect of leg muscle training on the speed of the kick taekwondo dollyo chagi in NTC Club Pontianak city; (2) this study aims to determine the increase in the speed of the kick taekwondo dollyo chagi in NTC Club Pontianak city after given leg muscle training. Materials and methods. The type used in this study is the type of quantitative research. This study is a way to measure the effect of leg muscle training using a test drill on the speed of the taekwondo dollyo chagi kick at the NTC Club Pontianak city, with a population of 8 male athletes in the junior class category. Samples used that have characteristics of male sex aged 15-17 years who are still actively training at the NTC Club Pontianak city with total sampling technique. Data collection techniques in the form of measurements and using a tool in the form of a Taekwondo Kick speed test dollyo chagi. The study was conducted for two months. Results. Based on the hypothesis of the effect of leg muscle training on the speed of taekwondo dollyo chagi kicks obtained a significant value of 0.2127 > 0.05 then H0 is accepted. Conclusions. (1) There is an effect of leg muscle strength training through drill exercises for each athlete on the speed of the dollyo chagi taekwondo kick at the NTC Club, Pontianak City; (2) There is an effect of muscle strength through drill exercises on each athlete on the speed of kicking taekwondo dollyo chagi at the NTC Club, Pontianak City.